Total Asset Turnover, Current Ratio, Pertumbuhan Laba dan Ukuran Perusahaan terhadap Return Saham pada Perusahaan Otomotif - William Jauhary; Andoro Ongario; Alvin Alvin (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine and analyze the effect of total asset turnover, current ratio, company profit growth and company size on stock returns on automotive listed on the Indonesia Stock Exchange for the period 2017 - 2020. This research method is quantitative. The sampling method is purposive sampling, a sample of 5 automotive companies listed on the Indonesia Stock Exchange for the 2017 - 2020 period multiplied by the 4 year period in the study. The data analysis method used in this study is Multiple Linear Regression Analysis. The results showed, a) the variable total asset turnover on stock returns has a value of tcount> ttable, namely 2.704 > 1.724 and a significant 0.005 <0.05; b) the current ratio variable to stock returns has a tcount > ttable, namely 1.928 > 1.724 and a significant 0.034 <0.05; c) the variable earnings growth on stock returns has a tcount > ttable, namely 2.898 > 1.724 and a significant 0.023 <0.05; d) the company size variable on stock returns has a value of tcount > ttable, namely 1.854 > 1.724 and a significant 0.028 <0.05. In conclusion, partially total asset turnover, current ratio, profit growth and company size have a significant effect on stock returns on automotive listed on the Indonesia Stock Exchange for the 2017-2020 period. As well a simultaneously total asset turnover, current ratio, profit growth and company size have a significant effect on stock returns in automotive companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Keywords: Current Ratio, Profit Growth, Stock Return, Total Asset Turnover, Company Size